Analisis Kinerja Routing Multi-Copy dengan Manajemen Buffer Shortest Life First (SHLI), Packet Priority dan Stationary Relay Node Pada Delay Tolerant Network (DTN) - Desman Desman; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The exchange of information via the internet is becoming the most effective medium today. Information connection via the internet Relating to an adequate internet connection. Some places that do not yet have adequate connectivity to the Kerinci mountain climbing route, make the transfer of information difficult because of high losses and large delays. Delay Tolerant Network (DTN) is a technology used on networks that are not always available. Using this type of multi-copy routing on DTN has advantages that can increase the delivery ratio and reduce the acquisition of this routing will require greater network resources. The buffer management policy can be used to optimize the use of limited buffers. Stationary Relay Node and Packet Priority can be used to increase the probability of sending messages. This research analyzes the performance of Multi-Copy routing with Shortest Life First buffer management, Packet Priority, and Stationary Relay Node supported using ONE simulator. Overhead Ratio, Delivery Probability and Average Latency in Spray and Wait, Epidemic and ProPHET routing. The results show the Spray and Wait for a route to get the best from the other route with an Overhead Ratio value of 5.0081, Delivery Probability of 0.9508 and an Average Latency of 1808.5116.